The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d2cp05771a
|View full text |Cite
|
Sign up to set email alerts
|

Charge and energy transfer dynamics in single colloidal quantum dots/monolayer MoS2 heterostructures

Abstract: Charge and energy transfer dynamics in Colloidal CdSeTe/ZnS quantum dots (QDs)/monolayer molybdenum disulfide (MoS2) heterostructures have been investigated by time-resolved single-dot photoluminescence (PL) spectroscopy. Time-gated method is used to separate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…There was obvious spectral overlap between the absorption spectrum of WS 2 and the emission spectrum of CQDs (see Figure S7). It was suggested that PL quenching of CQDs may originate from the energy transfer between CQD–WS 2 composites. Energy transfer efficiency (η) can be calculated by below formula η = k ET k r + k nr + k ET = I 0 I I 0 where I 0 and I is the PL intensity at the peak of 490 nm of CQDs alone and the CQD–WS 2 composites. k r and k nr are the radiative and nonradiative recombination rates of photogenerated excitons, which are intrinsic properties of CQDs that are unaffected by WS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…There was obvious spectral overlap between the absorption spectrum of WS 2 and the emission spectrum of CQDs (see Figure S7). It was suggested that PL quenching of CQDs may originate from the energy transfer between CQD–WS 2 composites. Energy transfer efficiency (η) can be calculated by below formula η = k ET k r + k nr + k ET = I 0 I I 0 where I 0 and I is the PL intensity at the peak of 490 nm of CQDs alone and the CQD–WS 2 composites. k r and k nr are the radiative and nonradiative recombination rates of photogenerated excitons, which are intrinsic properties of CQDs that are unaffected by WS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The potential mechanisms behind the observed PL enhancement include photoexcited CT and Förster resonance energy transfer (FRET). [38] Si QDs exhibit a longer luminescent decay time (%μs) due to their quasi-direct-bandgap nature with indirect-gap properties, which may rule out the possibility of FRET due to unfavorable harmonics between light decay and subsequent absorption. [39][40][41][42] Therefore, we attribute the dominant mechanism of PL enhancement to CT following the decoration of Si QDs.…”
Section: Resultsmentioning
confidence: 99%
“…Many other antenna systems have demonstrated extremely high energy transfer efficiencies such as photosynthetic antenna complexes and light harvesting nanotubes. , The energy concentration from large area 2D to 0D semiconductors of the same composition, however, has not been previously explored to our knowledge. It has been shown from 2D TMDs to separately synthesized nanocrystals such as WS 2 to PbS-CdS, WS 2 to CdSe/ZnS, and MoS 2 to CdSeTe/ZnS, as well as in InGaAs quantum wells to CdSe/ZnS QDs. ,,, In NPLs, energy transfer from 2D to 0D has been demonstrated from CdSe NPL to metallic nanoparticles such as Pt, Pd, and Au. ,,, Similarly, energy transfer from 2D NPLs to molecular chromophores has been demonstrated such as in 3 ML CdSe NPLs to conjugated fluorophores . These results are summarized in Figure b, where the QE is shown as a function of acceptor density (or the number of reported acceptors per area of donor).…”
Section: In Situ Grown Hgte Npl/qd Heterostructurementioning
confidence: 99%
“…Finally, in Figure 5 we compare the theoretical diffusion constant (indicated by an asterisk) to 27,28 oligoacene triplets and singlets, 29 nanotubes, 30−32 2D semiconductors, 33−40 and nanoplatelets 41,42 at room temperature. b) Energy transfer efficiency rates for 2D to 0D systems including TMDs and quantum well (QW) to NCs, 3,43,44 NPLs to NCs, 18,45 our and NPLs to conjugated fluorophores. 46 The Journal of Physical Chemistry Letters Many other antenna systems have demonstrated extremely high energy transfer efficiencies such as photosynthetic antenna complexes and light harvesting nanotubes.…”
Section: The Journal Ofmentioning
confidence: 99%
See 1 more Smart Citation